The Influence Of Millennial Leadership In The 4.0 Era On Employee Performance - Komara, Edi (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2024)
The purpose of this research is to determine the influence of leadership style, motivation and work environment on PT XYZ employee performance.. The method used in this research is the data collection method through a questionnaire which is measured using a Likert scale diagram. The sampling method used a saturated sampling technique using all employees as the population and obtained 62 respondents. This research is quantitative research using an associative strategy. Data processing using SPSS version 25 for Windows with Multiple Linear Regression Test. This multiple linear regression analysis test aims to determine the relationship between Leadership Style, Work Motivation and Work Environment which influence employee performance. The results of the research show that Leadership Style, Work Motivation, and Work Environment partially have a positive and quite significant effect on Employee Performance.